STRUGGLE IN FORMAL EDUCATION BY DOMESTIC-WORKER STUDENTS - Budhathoki, Boj Bahadur (International Journal of Research -GRANTHAALAYAH, 2020)
The various concept in education such as “Education for All (EFA)”, “Equity in Education”, “Inclusive Education” are the burning issues as well as implementation complexities in today’s education system in developing countries. Stepping on these issues, this article focuses on seeking equity in education in the Nepalese community schools. Education for all is an ongoing process in globally. Under the national and international education framework, Nepal is on the process of implementation of the School Sector Development Program (SSDP). But, equity in education is still far behind for some groups of students. Here, this study intends to focus on, one of the similar groups of students, who are living as domestic-worker and continuing their study at the school level. This study tries to throw light on the learning-struggle of a particular group of students in Nepali community schools. The study is based on the experiences of 7 domestic-worker students (DWS) and 3 teachers teaching them. The DWS faced numerous labor exploitation problems in the workplace and school premises.